Fusaric Acid Induces DNA Damage and Post‐Translational Modifications of p53 in Human Hepatocellular Carcinoma (HepG2) Cells. Issue 11 (19th May 2017) - Ghazi, Terisha; Nagiah, Savania; Tiloke, Charlette; Sheik Abdul, Naeem; Chuturgoon, Anil A.
ABSTRACT: Fusaric acid (FA), a common fungal contaminant of maize, is known to mediate toxicity in plants and animals; however, its mechanism of action is unclear. p53 is a tumor suppressor protein that is activated in response to cellular stress. The function of p53 is regulated by post‐translational modifications—ubiquitination, phosphorylation, and acetylation. This study investigated a possible mechanism of FA induced toxicity in the human hepatocellular carcinoma (HepG2 ) cell line. The effect of FA on DNA integrity and post‐translational modifications of p53 were investigated. Methods included: (a) culture and treatment of HepG2 cells with FA (IC50 : 580.32 μM, 24 h); (b) comet assay (DNA damage); (c) Western blots (protein expression of p53, MDM2, p‐Ser‐15‐p53, a‐K382‐p53, a‐CBP (K1535)/p300 (K1499), HDAC1 and p‐Ser‐47‐Sirt1); and (d) Hoechst 33342 assay (apoptosis analysis). FA caused DNA damage in HepG2 cells relative to the control ( P < 0.0001). FA decreased the protein expression of p53 (0.24‐fold, P = 0.0004) and increased the expression of p‐Ser‐15‐p53 (12.74‐fold, P = 0.0126) and a‐K382‐p53 (2.24‐fold, P = 0.0096). This occurred despite the significant decrease in the histone acetyltransferase, a‐CBP (K1535)/p300 (K1499) (0.42‐fold, P = 0.0023) and increase in the histone deacetylase, p‐Ser‐47‐Sirt1 (1.22‐fold, P = 0.0020). The expression of MDM2, a negative regulator of p53, was elevated in the FA treatment compared to the control (1.83‐fold, P < 0.0001). FA also inhibited cell proliferation and induced apoptosis in HepG2 cells as evidenced by the Hoechst assay. Together, these results indicate that FA is genotoxic and post‐translationally modified p53 leading to HepG2 cell death. J. Cell. Biochem. 118: 3866–3874, 2017. © 2017 Wiley Periodicals, Inc. Abstract : FA is genotoxic and post‐translationally modified p53 leading to cell growth arrest and apoptosis of HepG2 cells. The results indicate that Ser‐15 phosphorylation is required for the function of p53 and this may suggest a possible universal role in promoting p53‐transcriptional activity.